HINGEneering IgG for enhanced immune activation - Werner, Anja; Nimmerjahn, Falk (Science immunology, 2022)
Two recent studies in Science Immunology by Orr et al. and Foss et al. demonstrate that the hinge region of immunoglobulin G (IgG) is a major regulator of IgG2 and IgG3 activity, respectively. Engineering of the IgG hinge may therefore be useful for optimizing the activity of IgG subclasses.
CRIS-Team Scopus Importer:2022-08-05